Political Economy and Information Capitalism in India
XIII, 242 p.
Keywords: In this theoretically and empirically engaging volume, the contributors demonstrate that despite the dynamism of India's software industry and the rhetorical flourishes of industry leaders, at present, the benefits of the revolution in information and communication technologies (ICTs) touch only the hundreds of thousands with the right skills and access. India still needs to do more to bring the benefits of ICTs to the hundreds of millions of its citizens still living in acute poverty. The contributors take stock of the political economy implications of informational development in India.